Surface Atoms Analysis of Silver Nanostructures by X-Ray Photoelectron Spectroscopy - Zahoor, A.; Qiu, T.; Choudhary, M.A.; Li, X. (Asian Journal of Chemistry, 2015)
The binding energy of silver 1D and 3D nanostructures, limited to the surface atoms within the range of 2 nm was analyzed by X-ray photoelectron spectroscopy (XPS). The surface scanning by XPS of silver nanostructures was made possible by polymer encapsulation. The synthesis of nanostructures and their surface encapsulation was obtained in non-aqueous medium under inert and dark environment to avoid the surface oxidation. Experimental data was comparatively analyzed which revealed that binding energy of surface atoms of silver nanoparticles and silver nanowires are comparable, with only intensity difference. The intensity of silver nanoparticles was found much higher as compared to silver nanowires due to their more surface exposition. Moreover, the IR data revealed that bending mode of vibrations are suppressed when polymer layer is thin and appeared well morphed when layer thickness was increased. The morphology of product was confirmed by transmission electron microscope.